Ribonuclease M5 Has Few, If Any, mRNA Substrates in Bacillus subtilis - Condon, Ciarán (American Society for Microbiology, 2002)
In Bacillus subtilis, maturation of 5S rRNA is catalyzed by an enzyme called RNase M5. We searched for potential mRNA substrates for RNase M5 by gene array technology, based on the premise that most endonucleolytic cleavages have an effect on the stability of RNA and hence on steady-state levels of expression. Only a handful of genes had significantly altered expression in rnmV mutants compared to wild-type strains that could subsequently be confirmed by Northern blotting. The effect of RNase M5 on the expression of the best candidates, the odhAB and sucCD operons, is indirect, by a mechanism we do not yet understand. We show that an effect of RNase M5 on the expression of the remaining candidate, ctsR, is due to the failure to process the 5S rRNA contained in the rrnW lying directly upstream. We thus conclude that RNase M5 has very few or possibly no mRNA substrates in B. subtilis.